SPEChpc 2021 Benchmarks on Ice Lake and Sapphire Rapids Infiniband Clusters: A Performance and Energy Case Study - Afzal, Ayesha; Hager, Georg; Wellein, Gerhard (14th IEEE/ACM Workshop on Performance Modeling, Benchmarking and Simulation of High Performance Computer Systems (PMBS23), 2023)
In this work, fundamental performance, power, and energy characteristics of the full SPEChpc 2021 benchmark suite are assessed on two different clusters based on Intel Ice Lake and Sapphire Rapids CPUs using the MPI-only codes' variants. We use memory bandwidth, data volume, and scalability metrics in order to categorize the benchmarks and pinpoint relevant performance and scalability bottlenecks on the node and cluster levels. Common patterns such as memory bandwidth limitation, dominating communication and synchronization overhead, MPI serialization, superlinear scaling, and alignment issues could be identified, in isolation or in combination, showing that SPEChpc 2021 is representative of many HPC workloads. Power dissipation and energy measurements indicate that the modern Intel server CPUs have such a high idle power level that race-to-idle is the paramount strategy for energy to solution and energy-delay product minimization. On the chip level, only memory-bound code shows a clear advantage of Sapphire Rapids compared to Ice Lake in terms of energy to solution.<br